Reimagining the Educated Citizen - Hendry, Petra Munro (Michigan State University Press, 2026)
Reimagining the Educated Citizen contends that the constructs of public education and citizenship in the struggle to constitute a U.S. national identity are inseparable from the simultaneous emergence of transatlantic constructs of an educated citizen along transnational and transracial lines. The nineteenth century is commonly understood as the age of nationalism and nation formation in which the Anglo-Protestant Common School movement takes center stage in the production of the American democratic citizen. Ironically, the argument for public, Common Schools privileged whiteness instead of equality. This book suggests that an alternative vision of the relationship between education and citizenship emerged from a larger transatlantic history. Given shape by the movement of people, ideas, commodities, and practices across the Caribbean, Africa, Europe, the Gulf of Mexico and the Mississippi Valley, this radical egalitarian vision emerged at the crossroads of the Atlantic-colonial and antebellum Louisiana.